2009
DOI: 10.1111/j.1475-097x.2009.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow mediated vasodilation and circulating concentrations of high sensitive C‐reactive protein, interleukin‐6 and tumor necrosis factor‐α in normal pregnancy – The Cardiovascular Risk in Young Finns Study

Abstract: Improvement of FMD in normal pregnancy was not affected by increase in hsCRP concentration. We found an association with IL-6 and FMD but we believe that improvement in endothelial function during normal pregnancy is not caused by variation in hsCRP, IL-6 or TNF-alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
2
15
2
Order By: Relevance
“…Previous studies also show enhanced endothelial function during pregnancy despite concurrent hyperlipidemia and metabolic changes (25), an effect which may carry over postpartum. Endothelial dysfunction is a hallmark of vascular diseases and hypertension, and is predictive of future cardiovascular events (26).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies also show enhanced endothelial function during pregnancy despite concurrent hyperlipidemia and metabolic changes (25), an effect which may carry over postpartum. Endothelial dysfunction is a hallmark of vascular diseases and hypertension, and is predictive of future cardiovascular events (26).…”
Section: Discussionmentioning
confidence: 87%
“…Potential mechanisms underlying a direct biological effect of pregnancy on atherosclerosis may include the transient hemodilution of pregnancy or increases of lipids, insulin resistance, oxidative stress, sex steroids, and inflammation during pregnancy. 7,8 In contrast, endothelial function is improved and asymmetrical dimethylarginine decreased during pregnancy, both of which would be expected to slow the progression of atherosclerosis. 8,25 Childbearing or Child-Rearing: Insights Derived From Males…”
Section: Childbirth and Cimt Progression: Other Potential Mechanismsmentioning
confidence: 99%
“…7,8 In contrast, endothelial function is improved and asymmetrical dimethylarginine decreased during pregnancy, both of which would be expected to slow the progression of atherosclerosis. 8,25 Childbearing or Child-Rearing: Insights Derived From Males…”
Section: Childbirth and Cimt Progression: Other Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…An early study reported a progressive increase in CRP across the weeks of gestation (Romem and Artal 1985). Others have reported that CRP is already high in early pregnancy (Sacks et al, 2004), remains elevated at a similar level into later pregnancy (Belo et al, 2005; Picklesimer et al, 2008), or that CRP peaks in mid-pregnancy (Saarelainen et al, 2009). Although at least one study reported ethnic differences in pregnancy CRP (Picklesimer et al, 2008), little is known about the extent of human variation in the magnitude or timecourse of inflammatory changes during pregnancy.…”
mentioning
confidence: 99%